2018
DOI: 10.3390/v10080420
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Virus Infection of Human Lymphocytes Occurs in the Immune Cell Cluster of the Developing Antiviral Response

Abstract: Monocytes-macrophages and lymphocytes are recruited to the respiratory tract in response to influenza virus challenge and are exposed to the virus during the establishment of immune defenses. The susceptibility of human lymphocytes to infection was assessed. The presence of monocytes-macrophages was required to attain infection of both resting and proliferating lymphocytes. Lymphocyte infection occurred in the context of immune cell clusters and was blocked by the addition of anti-intercellular adhesion molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 75 publications
(98 reference statements)
1
16
0
Order By: Relevance
“…Lymphocyte infection was decreased in a dose-dependent manner when anti-intercellular adhesion molecule-1 (ICAM-1) antibody was added to PBMC cultures to prevent clustering between monocytes/macrophages and lymphocytes. The studies also demonstrated that both peripheral blood lymphocytes and human alveolar lymphocytes required the presence of monocytes/macrophages for infection to occur [24]. Both CD4+ and CD8+ lymphocytes, and both resting and proliferating lymphocytes, became infected only when exposed to IAV in the presence of monocytes/macrophages.…”
Section: Human Monocytes/macrophages Are Directly Responsible For Lymmentioning
confidence: 84%
See 2 more Smart Citations
“…Lymphocyte infection was decreased in a dose-dependent manner when anti-intercellular adhesion molecule-1 (ICAM-1) antibody was added to PBMC cultures to prevent clustering between monocytes/macrophages and lymphocytes. The studies also demonstrated that both peripheral blood lymphocytes and human alveolar lymphocytes required the presence of monocytes/macrophages for infection to occur [24]. Both CD4+ and CD8+ lymphocytes, and both resting and proliferating lymphocytes, became infected only when exposed to IAV in the presence of monocytes/macrophages.…”
Section: Human Monocytes/macrophages Are Directly Responsible For Lymmentioning
confidence: 84%
“…Notably, the initiation of an immune response to IAV challenge involves the development of immune cell clusters between PBM and lymphocytes [23,24]. This challenge-induced structure provides the opportunity for PBM to act as accessory cells for the presentation of viral antigens to lymphocytes.…”
Section: Dichotomy In the Human Monocyte/macrophage Antigen-presentinmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously showed that human monocyte/macrophage and lymphocyte interaction after exposure to influenza virus, including H1N1, H2N2 and H3N2 strains, is required for synthesis of viral proteins by lymphocytes [ 15 , 16 ]. In recent studies, we have used cells from individuals who were on a panel of slightly more than 100 subjects who had been serologically HLA-typed.…”
Section: Resultsmentioning
confidence: 99%
“…The current studies were undertaken in response to some surprising HLA-related results in studies of the requirement for monocyte/macrophage participation for influenza virus infection of human lymphocytes [ 15 , 16 ]. Those studies showed that influenza virus infection of human lymphocytes occurs in the immune cell cluster of the developing antiviral response.…”
Section: Introductionmentioning
confidence: 99%